Public Relations Efforts In Building Brand Awareness Image of TikTok Shop - Waheri, Sulis (Institut Agama Islam Negeri Kendari, 2024)
The rapid development of technology, particularly the internet, has transformed the landscape of business and public relations. Social media platforms like TikTok have become essential tools for global marketing and online communication. This study examines the role of Public Relations in enhancing brand awareness of TikTok Shop, an integral part of the TikTok ecosystem, using a qualitative approach based on interviews with Public Relations professionals and analysis of TikTok Shop’s campaigns. The findings indicate that interactive campaigns, influencer collaborations, and engaging content effectively boost brand recognition and consumer engagement. However, challenges such as building trust and ensuring consistent messaging persist. This research highlights the strategic importance of Public Relations in shaping brand identity and enhancing TikTok Shop’s appeal. The insights offer practical implications for marketers, emphasizing the need to leverage social media for sustained brand growth and consumer loyalty.Keywords: Brand Awareness, Public Relations, Qualitative Research, Social Media Strategies, TikTok Shop.